Reporte de referencias bibliográficas de hospedaje estudiantil (2021)
In this work we will find information from different consultations of the different results of the theme of research on student lodging that were made by other university students from different university careers at the international. Which we can find in their work a wide variety of contents to be able to solve in which the stay of students is considered where They are given some solutions so that they have a place to live and where to spend the night since studying requires a stay in a place where the university is located possible close to an approximate distance to it. and be able to solve your needs domestic order in which they require to see where to put their books where to study in their free hours, where they feed, of course, in the surroundings of the universities, not in all but in most of them there are a chain of restaurants and businesses that provide services to the alma mater and its surroundings but it is that in most of cases they take their food to eat in their places where they they find living in order to lead a normal life. but we're not going to talk about that this job the point is to solve your needs of where to stay and your stability experiential in what has to do with the hosting architectural solution to carry out their study matters and carrying out work and other academic obligations of higher education